2019
DOI: 10.1093/mnras/stz1080
|View full text |Cite
|
Sign up to set email alerts
|

Virgo: an unlikely cluster of galaxies because of its environment

Abstract: Galaxy clusters constitute powerful cosmological probes thanks to comparisons between observed and simulated clusters. As such Virgo constitutes a formidable source for detailed observations facilitated by its proximity. However, the diversity of clusters complicates the comparisons on a one-to-one basis. Simulated clusters must be carefully selected, a daunting task since most properties are unknown. Alternatively, lookalikes produced in the proper large scale environment can be used. Additionally, their stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…At a distance of just ∼16-18 Mpc (Mei et al 2007;Planck Collaboration et al 2016) from Earth, and sitting in the middle of the northern Spring sky, Virgo has been the primary target of most gas surveys focusing on understanding the role of environment on the gas cycle of galaxies. Given that Virgo may not be the average nearby cluster, at least in terms of accretion history and number of substructures (Sorce, Blaizot, & Dubois 2019), this is something to keep in mind.…”
Section: The Case For Hi Strippingmentioning
confidence: 99%
“…At a distance of just ∼16-18 Mpc (Mei et al 2007;Planck Collaboration et al 2016) from Earth, and sitting in the middle of the northern Spring sky, Virgo has been the primary target of most gas surveys focusing on understanding the role of environment on the gas cycle of galaxies. Given that Virgo may not be the average nearby cluster, at least in terms of accretion history and number of substructures (Sorce, Blaizot, & Dubois 2019), this is something to keep in mind.…”
Section: The Case For Hi Strippingmentioning
confidence: 99%
“…Namely, while the Virgo-like clusters used to accrete lots of objects in their early stages of evolution, nowadays they still do but to a much smaller extent. In a more recent study (Sorce et al 2019) that enlarged our previous sample from 15 to 200 Virgo counterparts and increased their resolution by a factor of 3, we found that this kind of assembly history is rare and that this is most probably due to the local environment. This study compared the properties of more than 400 cluster-size random halos to the 200 Virgo-like halos.…”
Section: Introductionmentioning
confidence: 58%
“…Local observational data used to constrain the initial conditions of the simulations are distances of galaxies and groups converted into peculiar velocities (Sorce & Tempel 2018;Sorce et al 2016b) that are bias minimized (Sorce 2015). The details of the algorithms and steps to get the simulations are given in Sorce et al (2019).…”
Section: Constrained Simulations and Virgo-like Halosmentioning
confidence: 99%
“…Note that most simulations of "MW type galaxies" are not random but require either quiet merger histories or isolation. What is perhaps surprising is that constrained simulations based on measurement of the local velocity field has already been shown to produce significantly and systemically different mass accretion histories for the simulated Virgo cluster (Sorce et al 2016c(Sorce et al , 2019. Here a similar behaviour is seen on mass scales that are 2 orders of magnitude smaller.…”
Section: The Mass Accretion History Of the Hestiamentioning
confidence: 95%
“…2.1). The CosmicFlows database and catalogue have been used extensively before to study the local universe, including the cold spot repeller (Courtois et al 2017), the Vela super cluster (Courtois et al 2019), the bulk flow (Hoffman et al 2015), and the Virgo cluster (Sorce et al 2016c(Sorce et al , 2019Olchanski & Sorce 2018). As will be demonstrated below, producing such constrained simulations is not trivial but will provide an optimum testing ground for understanding both the role of our environment in shaping the LG as well as the holistic formation of LG galaxies.…”
Section: Introductionmentioning
confidence: 99%